2019
DOI: 10.1002/term.2904
|View full text |Cite
|
Sign up to set email alerts
|

Improved neural differentiation of normal and abnormal induced pluripotent stem cell lines in the presence of valproic acid

Abstract: During the generation of induced pluripotent stem cell (iPSC) lines from cord blood CD34+ cells, a line having complete trisomy of Chromosome 1 and deletion of q23 to qTer of Chromosome 11 was accidentally developed in our lab. The abnormality was consistently detected even at higher passages. These chromosomal anomalies are known to manifest neurological developmental defects. In order to examine if such defects occur during in vitro differentiation of the cell line, we set up a protocol for neural differenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…VPA has been used to promote the differentiation of human stem cells into different types of somatic cells. It improved neural differentiation of human iPSCs [23], ESCs [24], mesenchymal stem cells [25] and adipose-derived stem cells [26], also hepatic and cardiomyocyte differentiation of human stem cells [27,28]. We showed that VPA robustly elevated the SSCLC induction efficiency in the presence of GDNF and b-FGF, and the combination of low concentrations of VPA and VC achieved the highest SSCLC induction efficiency.…”
Section: Introductionmentioning
confidence: 80%
“…VPA has been used to promote the differentiation of human stem cells into different types of somatic cells. It improved neural differentiation of human iPSCs [23], ESCs [24], mesenchymal stem cells [25] and adipose-derived stem cells [26], also hepatic and cardiomyocyte differentiation of human stem cells [27,28]. We showed that VPA robustly elevated the SSCLC induction efficiency in the presence of GDNF and b-FGF, and the combination of low concentrations of VPA and VC achieved the highest SSCLC induction efficiency.…”
Section: Introductionmentioning
confidence: 80%
“…VPA was evaluated in this protocol for several reasons. The effect of VPA has been assessed in various studies of multipotent and pluripotent cells towards neuronal differentiation, however the biological mechanism and pathways have not been identified (Duan et al, 2019; Fernandes et al 2019). It has also been documented that VPA, as a histone deacetylase inhibitor, may create a neuroprotective niche (Dekker et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Differentiation toward the astrocytic lineage is decreased under these conditions, which is usually observed during differentiation to the neuronal lineage. Length and connections established by neurites are also significantly increased by VPA addition [115]. Besides, the use of retinoic acid (NaB) increases the acetylation of H3K9 at the PAX6 promoter, which promotes the induction of neural progenitor cells [116].…”
Section: Role Of Histone Acetylation and Deacetylationmentioning
confidence: 99%